Magnetic Dipole Localization Studies for Magnetoencephalography using Multiple Phase Inverse Analysis and Experimental Verification - Kishimoto, Yoshinao; Liu, Jeff; Cheung, Teresa; Parameswaran, Ash M.; Amaya, Kenji (CMBES Proceedings, 2009)
No Abstract